Små molekyler - Stor avkastning? - En studie av börsintroduktioners långsiktiga avkastning på den amerikanska läkemedelsbranschen - Sederowsky,Beatrice; Rödén,Marcus; Carlsson,Martin (2015)
The purpose of this thesis is to examine initial public offerings in the health care and whether they underperform or not in the long run. The correlation between the performance and chosen variables is to be tested. Earlier research shows that there generally is long-run underperformance present after an IPO, this study tests if this research is applicable in pharmaceuticals and biotechnology.
Keywords: IPO; underprestation; långsiktig prestation; läkemedelsbranschen; multipel regressionsanalys